Potential Utilization of Flue Gas Using Organic Rankine Cycle (Study Case PLTMG Balai Pungut-Duri) - Triyanti, Riska; Jelita, Marhama (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
PLTMG Balai Pungut-Duri is one of the largest gas engine type power plants in Riau with a capacity of 7x16 MW. The efficiency produced by the Balai Pungut-Duri PLTMG is 38% with the standards set by PT. PLN Efficiency in this type of generator is 45-47.5%. One of the factors that causes a reduction in the value of efficiency in power plants is that energy is converted into work and some is wasted, one of which is energy from flue gas. The purpose of this study is to examine the potential for utilizing flue gas using the Organic Rankine Cycle (ORC). The method used in this study is the law of thermodynamics 1 to determine the parameter values needed to determine the efficiency and power generated using the Engineering Equation Solver software. From the results of the calculations carried out, the Balai Pungut PLTMG produces an efficiency of 38.49% and a power of 14,530 kW under excited conditions. In utilizing flue gas using an organic rankine cycle it produces an efficiency of 19.97% with a power of 4,556 kW. the combined efficiency that can be produced by PLTMG Balai Pungut-Duri is 50.56% with a total power of 19,086 kW, with an efficiency increase of 12.07%. The results of the study show that the use of flue gas energy can increase efficiency according to PLN standards.